Security Analysis of the First Certificateless Proxy Signature Scheme Against Malicious-But-Passive KGC Attacks. (5th August 2020) - Lin, Xi-Jun; Wang, Qihui; Sun, Lin; Yan, Zhen; Liu, Peishun
Abstract: Recently, Yang et al. proposed the first certificateless proxy signature scheme against malicious-but-passive key generation center (MKGC) attacks. They proved that their scheme can resist the MKGC attacks in the standard model. In this paper, we point out that their scheme cannot achieve this security because the adversary can forge valid signatures.